2020
DOI: 10.1080/13621718.2019.1706810
|View full text |Cite
|
Sign up to set email alerts
|

Double-side friction stir welding of thick magnesium alloy: microstructure and mechanical properties

Abstract: A two-step double-side friction stir welding (DS-FSW) technique was proposed to join 20 mm thick Mg-Y-Nd magnesium alloy plates. FSW was first carried out on one side of the butt joint, and then the plates were left-right reversed for the other side welding. The DS-FSW joint was free of defects and the weld nugget zone (NZ) showed fine equiaxial grains. An overlap zone with ultrafine grain ( ∼ 2.19 µm) and dispersive particles existed between the two welding tracks, beneficial to the integrity of the joint. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…They observed the formation of random crystallographic texture in DS‐FSW which improved the strength and ductility of the joints. Weng et al [ 18 ] in their study on DS‐FSW of Mg alloy plates of 20 mm thickness observed the finer equiaxed grains in overlap region and similar texture distribution and comparative hardness with parent material.…”
Section: Introductionmentioning
confidence: 97%
“…They observed the formation of random crystallographic texture in DS‐FSW which improved the strength and ductility of the joints. Weng et al [ 18 ] in their study on DS‐FSW of Mg alloy plates of 20 mm thickness observed the finer equiaxed grains in overlap region and similar texture distribution and comparative hardness with parent material.…”
Section: Introductionmentioning
confidence: 97%
“…Increasing interest has been seen, especially over the past two decades, in solving problems related to joining of various types of magnesium alloys [13][14][15][16][17][18][19][20]. Porosity [13,14] and hot cracking [15,21] were identified as major problems in welding of magnesium alloys.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the FSW of thick Mg extruded flats poses much greater difficulty because of the brittle nature of Mg alloys. Yet, progress towards thick section FSW of magnesium alloys is also being made, as few studies have recently been reported in this regard [22]. Such progress is largely directed towards weight reduction in aircrafts and automobiles to improve fly-to-buy ratios and fuel economies.…”
Section: Introductionmentioning
confidence: 99%